A Study of Quality of Life: A Comparative Study with Respect to Gender and Residence of Cancer Patients of India - Husam Awad Odeh Alsarhan (International Journal of Advanced Science and Technology, 2020)
The World Health Organization (WHO) describes the quality of life like, individual insight if their position in life span in the framework of the culture and value system in which they live and in relation to their goals, expectations, standards and concerns (Awan, Waqas, Aslam, & Abbas, 2011). There are a limited number of researches conducted on gender and quality of life throughout the world and especially in India. Therefore, this cross-sectional research is one of the initial attempts to study the role of gender on quality of life among cancer patients. Objective: The aim of this study is to examine the role of gender on quality of life among cancer patients of India. Methods: A sample of 90 cancer patients (male=45 & female=45) were selected from AIIMS Delhi by using purposive sampling procedure. The sample was further divided on the basis of residence viz. (rural 35 and Urban 55). The short version (WHOQOL- BREF) of World Health Organization Quality of Life Questionnaire, was used in the present study. There are four domains of this quality of life scale which include physical health, social relationships, psychological health and environmental domain. Independent sample t-test was used for the analysis of the data. The SPSS (20.00 version) was the software which was used for analysis of the study. Results: The results of this study revealed that there is a significant mean difference in physical health (dimension of Quality of Life Scale) between male and female cancer patients. However, no significant difference was found between male and female cancer patients on social relationships, psychological health, environmental domain and overall quality of life.physical health Moreover, physical health, psychological health, environmental domain and overall quality of life was found high in urban cancer patients and social relationships was found high in rural cancer patients. Conclusion: The results of the present study revealed that female cancer patients were found high on physical health and males were found low on this dimension. Researchers have to take initiatives in order to build intervention programmes for the sample.